Penerapan Keterampilan Membuka dan Menutup Pembelajaran Sebagai Strategi Pembelajaran Aktif di Kelas - Sofiah Sofiah; Ira Wardani Nst; Alvini Riska Wardani; Kholidah Nur (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
The skill of opening and closing learning is a basic skill that is important for teachers to have in order to achieve effective and enjoyable learning. Opening a lesson is an activity carried out by teachers/infrastructure to create an atmosphere of mental readiness and full attention to students/participants. Closing a lesson (closure) is an activity carried out by teachers to end a lesson or teaching and learning activity by restating the main points of the lesson. This study uses a qualitative approach with a library research design, thus this study was conducted by examining reading sources that are related to the study being discussed. Data collection was carried out by searching through literature reviews from reading books, journals and sources from the Google School Digital Library and online libraries. The results of this study are to determine what skills a teacher must have in opening and closing learning.